Development to Motivate the Interest and Ability of Entrepreneurship of Medika Suherman University Students - Septia B., Rico; Nurhasan, Nurhasan (LPPM Universitas Bumigora, 2023)
Indonesia is a large country, but the proportion of entrepreneurs in the population is very small. Empirical facts show that the number of university graduates has increased significantly over time, while the absorption capacity of the labor market is very low. So it is deemed necessary to develop student entrepreneurship. The purpose of this activity is to provide information about entrepreneurship and increase interest in entrepreneurship for students. The PkM team helps activity participants to be motivated and have an interest in the business world through the provision of material delivered by the speakers. The PkM team also helps provide assistance and training to activity participants. Based on the PkM activities that have been carried out, it is concluded that